The role of corticotrophin-releasing hormone in the diagnosis of Cushing's syndrome - Peters, C; Storr, H; Grossman, AB; Savage, M (2006)
Background: Corticotrophin-releasing hormone (CRH) was identified by Vale and co-workers in 1981 and has since been used extensively in the diagnosis of ACTH-dependent Cushing's syndrome (CS). It was hoped that the CRH test would discriminate between pituitary and ectopic ACTH secretion. In adults, a rise from basal to peak plasma cortisol of ≥ 20% and ACTH of ≥ 50% is consistent with Cushing's disease (CD). Methods: Twenty-seven paediatric patients, with CD (mean age ± S.D. 13.1 ± 3.2; range 6.4-17.8 years) were investigated in our centre between 1982 and 2005. Results: During the CRH test, all patients showed an increase in cortisol of > 20% (range 106-554%). In one patient with ectopic ACTH syndrome, there was no increase in cortisol after CRH. In six paediatric patients with CS due to primary adrenal hyperplasia, no patient showed an increase in cortisol after CRH of > 1%. Conclusions: A further suggested use of CRH is to increase the sensitivity of the central to peripheral and interpetrosal ratios of ACTH during inferior petrosal sinus catheterisation (IPSS). Bilateral IPSS with human CRH (hCRH) has been performed in our unit in 21 children with CD, as part of the preoperative preparation prior to trans-sphenoidal surgery (TSS). Its principal role was to identify the site of the microadenoma. Sixteen of 21 patients (76%) who underwent IPSS with hCRH were cured following TSS. In our view, the CRH test is of value during IPSS by clarifying the position of the microadenoma and in this way contributed to the overall outcome of TSS in paediatric patients with CD. © 2006 Society of the European Journal of Endocrinology.